2003
DOI: 10.1007/s00192-004-1159-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective 3D ultrasonographic evaluation of immediate postpartum urine retention volume in 100 women who delivered vaginally

Abstract: Our objective was to determine the reproducibility and validity of urine retention volumes measured by 3D ultrasonography (3D-US) 2 h postpartum. This was a longitudinal prospective study of 100 women who delivered vaginally. Each woman underwent five successive urine retention measurements with the Bladder Scan 2 h after vaginal delivery, followed by transurethral catheterization to determine the real volume. The reproducibility of only the last four scan values was analyzed with an intraclass correlation coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Demaria et al found that using a commercial bladder scanner with a special 3D ultrasound probe is accurate for estimating immediate postpartum urine retention volume in women who delivered vaginally [22]. Using a commercial bladder scanner is not economical due to the high cost, and it only has a single function, i.e., to check the volume of bladder residual urine [23].…”
Section: Discussionmentioning
confidence: 99%
“…Demaria et al found that using a commercial bladder scanner with a special 3D ultrasound probe is accurate for estimating immediate postpartum urine retention volume in women who delivered vaginally [22]. Using a commercial bladder scanner is not economical due to the high cost, and it only has a single function, i.e., to check the volume of bladder residual urine [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the accuracy of bladder scanners in postpartum women. [3][4][5][6][7] However, only a few studies have been conducted in the United States. Some studies did not maintain consistent time intervals between bladder scanning and catheterization.…”
Section: Why This Mattersmentioning
confidence: 99%
“…Previous studies have investigated the accuracy of bladder scanners in postpartum women 3–7 . However, only a few studies have been conducted in the United States.…”
mentioning
confidence: 99%